Analisis Semiotika Komunikasi terhadap Interpretasi Pesan Motivasi dan Resiliensi dalam Lirik Lagu “Tapi” Band Perunggu - Nada Salsabila Setiawan; Amiruddin Saleh; Harvia Atika Zahira (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Song lyrics as part of popular culture not only serve as entertainment, but also serve as a medium for conveying social, psychological, and life values. One of the themes that often emerge in contemporary music is the experience of migration and resilience in facing the pressures of urban life. This study aims to uncover the construction of the meaning of motivation and resilience in the lyrics of the song